2022
DOI: 10.1089/neur.2021.0058
|View full text |Cite
|
Sign up to set email alerts
|

Early Transcutaneous Tibial Nerve Stimulation Acutely Improves Lower Urinary Tract Function in Spinal Cord Injured Rats

Abstract: Despite the fact that a majority of patients with an injury to the spinal cord develop lower urinary tract dysfunction, only few treatment options are available currently once the dysfunction arises. Tibial nerve stimulation has been used in pilot clinical trials, with some promising results. Hence, we investigated whether the early application of transcutaneous tibial nerve stimulation in the animal model of spinal cord injured rats can prevent the development of detrusor overactivity and/or detrusor-sphincte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…Sacral root stimulation has been used for years to improve micturition in SCI patients; however, is not widely applied due to its complexity. 98 Tibial nerve stimulation has been reported to be effective in treating neuropathic overactive bladder preclinically 99 and clinically. 100 , 101 In addition to promoting motor recovery, epidural stimulation has improved bladder function in several cases.…”
Section: Discussionmentioning
confidence: 99%
“…Sacral root stimulation has been used for years to improve micturition in SCI patients; however, is not widely applied due to its complexity. 98 Tibial nerve stimulation has been reported to be effective in treating neuropathic overactive bladder preclinically 99 and clinically. 100 , 101 In addition to promoting motor recovery, epidural stimulation has improved bladder function in several cases.…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration of CRH-ir axons occurs in lampreys with a high degree of functional recovery (Ayer’s test) and these regenerated axons not only regrow through the site of injury and for some millimeters caudally, but also re-establish pre-synaptic contacts with targets below the site of injury. In contrast, CRH projections from the Barrington’s nucleus are only partially recovered in lumbosacral levels 4 weeks after an incomplete spinal cord transection at T8/T9 (thoracic level) in rats [40] , which parallels bladder malfunction in these animals. Thus, our work provides a new model to understand spontaneous and successful axonal regeneration in a neurochemically-distinct neuronal population in lampreys, which in the past has mainly relied on the analysis of giant descending neurons by using tracer applications.…”
Section: Resultsmentioning
confidence: 93%
“…Restoration of urination control is one of the main aims in SCI patient management [39] . Importantly, CRH projections from the Barrington’s nucleus are only minimally recovered in lumbosacral levels 4 weeks after an incomplete spinal cord transection at T8/T9 (thoracic level) in rats [40] . In the spinal cord of mature larval sea lampreys, CRH neurons are only present in the most rostral spinal cord, close the rhombencephalon/spinal cord transition [34] .…”
Section: Introductionmentioning
confidence: 97%
“…Unlike the epidural method, transcutaneous stimulation is a non-invasive approach to spinal cord stimulation, which involves the placement of electrodes onto the surface of the patient’s skin. Furthermore, aside from this approach being less invasive, preliminary studies reported potential benefits in reducing muscle spasticity, improving residual motor functioning, and regulating autonomic functions, including heart rate, thermoregulation, and bladder sphincter function [ 69 , 70 ]. On top of experimental studies on animals, more clinical trials and human studies are needed to fully ascertain the advantages and long-term side effects of spinal cord stimulation for SCI [ 63 ].…”
Section: From Neuromodulation To Sensorimotor Rehabilitation Interven...mentioning
confidence: 99%